Distribución del presupuesto asignado al Gobierno Autónomo Descentralizado Parroquial Rural de Ricaurte - Alava Oñate, Ahiliz Mireya (2019)
The Decentralized Rural Parochial Autonomous Government of Ricaurte located in the Urdaneta Canton of Los Rios Province on Eduardo Obando Street (Malecon) between Vidal Miranda and Bartolome Bastidas is a public institution that has political, administrative and financial independence. The distribution of the budget made by Autonomous Decentralized Rural Parish Government of Ricaurte presents setbacks that are evidenced in the variation of the budget allocated by the State, so that said institution has to adjust times to the decrease of the budget granted through the Ministry of Economy and Finance, which does not ensure that the Rural Parish Government has sufficient financial resources to perform all its functions and powers